Protein quality in grain legumes grown in the lowland humid tropics, with special reference to West Africa - Luse, R.A.; Kang, B.T.; Fox, R.L.; Nangju, D. (International Potash Institute, 1975)
The grain legumes are important sources of dietary protein in the lowland humid tropics. To attain their yield potential and hence possible protein productivity, legumes grown in the lowland humid tropics (except on newly cleared land) require fertilizer Nand P. Observations in West Africa have indicated that seed yield and protein content have been raised in soybean by added Nand P. Rhizobial inoculation without fertilizer N increased seed protein from 31 to 36%. In terms of protein yield, inoculation is equivalent to 65 kg/ha of fertilizer N when used with 30 kg/ha'starter'N. Cowpea yield respon: ed to added Nand P but seed protein content was unaffected. Seed yield and seed S content of cowpea increased as the level of added soil solution S increased from near zero to about 2 ppm and then tended to remain nearly constant at higher soil S concentrations. Seed protein content was relatively unchanged. Protein content in groundnuts was not influenced by N, P or K fertilizer. The effect of K fertilization on seed yield and protein quality of grain legumes needs further investigation. Micronutrients, particularly B, Mo and Zn, may limit legume yield, but low yielding cultivars and low N PK fertilizer rates have tended to conceal this Iimitation.